Can Hba1c be a marker for cardiovascular risk in type 2 Diabetes Mellitus - Sreehari Dshmukh; V B Singh; Chetan Kumar Hb; Babulal Meena; Sanjay Beniwal; Vishnu Kumar Saini (International Journal of Medical Research and Review, 2015)
Introduction: One in every five Indians in geriatric age has diabetes. Diabetes is associated with increase in TG and apo B, with decrease in HDL component, so it contributes to atherosclerosis formation. We conducted a study to correlate glycaemic control using glycated haemoglobin with dyslipidaemia.Methods: The study is a cross sectional study with 200 diabetic patients, HbA1c was correlated with lipid profile and atherogenic index of plasma (AIP). AIP is log ratio of plasma triglyceride to HDL. Patients were categorised into good glycaemic control (<7%) and poor glycaemic control (>7%) based on glycaemic control with HbA1C as the marker.Results: Study showed the duration of diabetes directly correlates with HbA1c. None of the patients who had diabetes for more than 10 had HbA1c less than seven. BMI had direct association with HbA1c. HbA1c demonstrated a positive significant correlation with Total Cholesterol, LDL and a negative significant correlation with HDL. Atherogenic index of plasma directly correlates with HbA1c with mean AIP of 0.36+0.24 and 0.58+18 in good glycaemic control (GCC) and poor glycaemic control (PCC) respectively. Patients with HbA1c >7.0% had statistically significantly higher value of total cholesterol, LDL when compared with <7.0%.Conclusion: These findings clearly indicate that HbA1c can provide valuable supplementary information about the extent of dyslipidaemia, AIP. Screening for HbA1c estimation helps in preventing complications by achieving adequate glycaemic control. Thus, HbA1c can be used as a potential biomarker to identify patients with cardiovascular risk in Type 2 Diabetes Mellitus and can used as a guide for aggressive therapeutic approach.